Quantitative evaluation of sprayability and sag resistance of thin spray-on liners with low CO2 emissions for replacing shotcrete to seal coal mine roadway - Zhaoxu Diao; Laibo Li; Wei Zhao; Kai Ma; Lingchao Lu (Case Studies in Construction Materials)
Shotcrete used for gas sealing of coal mine roadway is easy to crack during micro-movement and the heavy use of shotcrete consumes a large amount of cement increasing CO2 emission. Thin spray-on liners (TSLs) with high elongation at break, less material consumables and low CO2 emissions can replace shotcrete as a sealing material. Improving the fluidity of TSLs paste to obtain excellent sprayability is a prerequisite for applications, however it also results in poor sag resistance of the TSLs. The quantitative evaluation of sprayability and sag resistance of TSLs paste is an important condition to measure whether the above contradiction is alleviated. In this paper, the dispersion degree (∆S), spray velocity (K) and sag rate (∆V) of TSLs paste with different cement-to-polymer mass ratio (C/P) were measured by using self-made spraying equipment for the first time. The relationships between ∆S and apparent viscosity, K and dynamic yield stress, and ∆V and static yield stress are established. The results showed that the ∆S, K and ∆V were key parameters for quantitative evaluation of sprayability and sag resistance of TSLs paste. The contradiction between sag resistance and sprayability of TSLs paste was alleviated when C/P was 1.5. The TSLs paste had the best sag resistance at the C/P1.5, meanwhile ∆V was reduced by 53.5 % compared with the C/P was 0.75. Compared to the C/P1.75 with optimal sprayability, the K and ∆S were only reduced by 10.5 % and 11.9 % when the C/P was 1.5. The CO2 emissions of TSLs was 95 % lower than that of shotcrete at the C/P1.5.